2007
DOI: 10.1139/s06-048
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of oxygen content of nappe, transition, and skimming flow regimes in stepped-channel chutes

Abstract: In a stepped-channel chute, the chute face is provided with a series of steps, from near the crest to the toe. Like many other high-speed flow configurations in hydraulic engineering, stepped-channel chute flows are characterized by the large amount of self-entrained air. Air entrainment on stepped-channel chutes is also recognized for its contribution to the oxygen transfer. The flow conditions in stepped-channel chutes have been classified into nappe flows, transition flows, and skimming flows. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 13 publications
1
9
0
3
Order By: Relevance
“…(5) of [22]; which indicated that critical depth increases with a decreasing value of aeration. Also, the result agrees with the statement of [24] that for all chute angle, aeration efficiency decreases with an increased in the ratio of critical depth to stepped height. The results in Figures 7a-7c, for the aeration efficiency as a function of the ratio of the length of aeration to the stepped roughness height, indicated that E20 increases as La/Ls increases.…”
Section: Determination Ofsupporting
confidence: 91%
“…(5) of [22]; which indicated that critical depth increases with a decreasing value of aeration. Also, the result agrees with the statement of [24] that for all chute angle, aeration efficiency decreases with an increased in the ratio of critical depth to stepped height. The results in Figures 7a-7c, for the aeration efficiency as a function of the ratio of the length of aeration to the stepped roughness height, indicated that E20 increases as La/Ls increases.…”
Section: Determination Ofsupporting
confidence: 91%
“…Berdasar pada penelitian yang dilakukan oleh Baylar, Bagatur, & Emiroglu, (2007), peningkatan jumlah tangga dan kemiringan pada muka hilir bending akan berpengaruh terhadap meningkatnya aerasi aliran. Ini artinya peningkatan aerasi akan berkaitan dengan peningkatan kadar DO pada aliran.…”
Section: ) Perhitungan Kadar Oksigen Terlarut Pada Bendung Bertanggaunclassified
“…Elle est souvent calculée à une température de référence de 20 °C en utilisant l'équation de GULLIVER et al (1990) : La majorité des études existantes (BAYLAR et al, 2006(BAYLAR et al, , 2007TOOMBES et CHANSON, 2005) n'intègrent pas la totalité des paramètres significatifs. De plus, les débits d'eau étudiés sont assez élevés et ne correspondent pas aux débits dans les petites rivières.…”
Section: Transfert D'oxygène Air-eauunclassified
“…Plus tard, TOOMBES et CHANSON (2005) ont étudié l'oxygénation sur un canal d'eau avec des marches d'escaliers à des dimensions proches de celles à l'échelle réelle. BAYLAR et al (2003BAYLAR et al ( , 2006BAYLAR et al ( , 2007 ont caractérisé l'oxygénation par des corrélations empiriques grâce à des mesures sur un pilote de laboratoire. Il existe d'autres approches qui ont été utilisées pour caractériser l'aération par les cascades.…”
Section: Introductionunclassified